STRATEGIC INNOVATION SYMPHONY: DRIVING COMBAT DRONES FOR DEFENSE ENHANCEMENT - Sarjito, Aris (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
As the landscape of warfare undergoes a transformative shift towards unmanned systems, combat drones emerge as pivotal instruments at the intersection of innovation, defense policy, and strategic orchestration. This research explores the intricate dynamics shaping combat drone development, emphasizing the harmonious interplay between defense policy and innovation theories. The rise of combat drones signals a paradigm shift in military strategies, necessitating a comprehensive understanding of the policy dynamics steering their innovation. This study aims to unravel the complex interdependencies between defense policies and innovation theories in combat drones' development, deployment, and strategic orchestration. This study uses various qualitative research methods to find its way through the complicated web of policy changes and new ideas in combat drone development. These methods include synthesis of literature reviews, content analysis of policy documents, case study examination, thematic coding of expert interviews, constant comparative analysis, and triangulation. Findings reveal the strategic symphony underlying combat drone evolution, illustrating the nuanced components shaping their trajectory. From policy harmonization to dynamic decision-making, the study illuminates the synergistic forces propelling combat drones for defense ascendance. In conclusion, the orchestration of defense policy and innovation theories intricately shapes the trajectory of combat drone technology. The synthesis of qualitative findings contributes to a holistic understanding of the strategic landscape, offering insights for policymakers, military strategists, and scholars navigating the complex realm of unmanned systems in defense.